A Typology of Transition-Age Youth - Raithel, Jessica; Wallace, Andrew; Schretzman, Maryanne; Johns, Eileen (International Journal of Population Data Science, 2018)
Young adulthood is a time of transition which poses particular challenges for youth who are homeless or at risk of homelessness, including those exiting foster care. The instability of being homeless puts youth at greater risk of many poor outcomes. Connection to relevant housing resources and services are critical to ensure that young adults have the opportunity to succeed. Better aligning youths’ needs with relevant housing resources can help young adults become and remain stably housed, leading to better lifetime outcomes. This study presents a typology of young adults who exit foster care and residential programs for homeless young adults, including emergency shelters and transitional living programs. The study uses administrative data to follow a cohort of 8,795 young adults, including young parents and unaccompanied young adults from ages 18 through 21, who exited foster care or homeless services. Using sequence analysis, subsequent service use after exit, including utilization of homeless services, hospitals, jail, subsidized housing, and supportive housing, was used to build three-year trajectories of service use patterns of youth. These patterns were then grouped together based on similarity using cluster analysis to form six distinct groups of youth: (1) Minimal Service Use, (2) Later Homeless Experience, (3) Earlier Homeless Experience, (4) Consistent Subsidized Housing, (5) Consistent Supportive Housing, and (6) Frequent Jail Stays. Profiles were developed for each typology to comprehensively, but concisely, describe differences in the characteristics of each group of youth. Models were also developed to determine factors that were predictive of each typology. This typology is being used to inform prioritization processes for housing resources and to better understand how to target programs based on potential pathways of youth.